أدب القصة القرآنية - الدكتور صاحب اسلام (الإيضاح, 2011)
Historical narratives of Prophets and nations in the Qur’an constitute a vital component in the revelation. These narratives could be studied, deliberated over, and investigated into from various angles such as religious, socio-political, historical. Besides messages of various natures, these historical narratives have literary value. If studied from literary angle, these historical narratives will stand